Acupuncture and Acupressure for Dementia Behavioral and Psychological Symptoms: A Scoping Review. (October 2020) - Harris, Melissa L.; Titler, Marita G.; Struble, Laura M.
Due to the dangers associated with psychotropic medications, there is an urgent need for non-pharmacologic therapies to treat behavioral and psychological symptoms of dementia (BPSD). Acupuncture and acupressure are safe and well-tolerated non-pharmacologic therapies for this population, but currently no review has explored acutherapy for management of distressing dementia symptoms. This review synthesizes research on acupuncture and acupressure for BPSD. Upon searching five databases, 15 studies met inclusion/exclusion criteria. Nine examined acupressure, six acupuncture, and eight were randomized controlled trials. The percent of studies demonstrating statistically significant improvements in symptoms were: activities of daily living (ADLs; 75%), agitation (100%), anxiety (67%), depression (100%), mood (100%), neuropsychological disturbances (67%), and sleep disturbances (100%). Variations in study design, intervention procedures, and outcomes limit interpretations about effectiveness. It is recommended that further research be done to examine the efficacy of these therapies and promote generalizability.